MN-MG DISORDERING IN CUMMINGTONITE: A HIGH-TEMPERATURE NEUTRON POWDER DIFFRACTION STUDY - Reece J.J.; Redfern S.A.T.; Welch M.D.; Henderson C.M.B. (My University, 2000)
The crystal structure of a manganoan cummingtonite, composition ([M4])(Na0.13Ca0.41Mg0.46Mn1.00) 102,614(2)(n) from Talcville, New York, has been refined at high temperature using in situ neutron powder diffraction. The P2(1)/m to C2/m phase transition, observed as spontaneous strains +epsilon(1) = -epsilon(2), occurs at similar to 107 degrees C. Long-range: disordering between Mg2+ and Mn2+! on the M(4) and M(2) sites occurs above 550 degrees C. Mn2+ occupies the M(4) and M(2) sites preferring M(4) with a site-preference energy of temperatures. Upon cooling, the ordered states of cation occupancy are 'frozen in' and strains in lattice parameters are maintained, suggesting that re-equilibration during cooling has not taken place.